Regret for Complaint Withholding. Issue 1 (1st January 2016) - Liu, Esther; Roloff, Michael E.
Abstract : This study examines regret for withholding relational complaints. The study sample of 393 participants completed measures of irritant frequency, irritant importance, relational intimacy, emotional distress from withholding, and regret for withholding. Irritant frequency mediated the positive relationship between length of withholding and irritant importance. This process predicted less intimacy and more emotional distress from withholding, the latter of which related to regret. Alternative paths were also found between length of withholding and regret. Results offer important implications for the role of regret management in hurtful confrontations and may inform other avoidance forms.